Carbapenem-resistant Acinetobacter baumannii carrier detection: a simple and efficient protocol - Jonathan Lellouche; Alona Keren-Paz; Reut Rov; Reut Efrati Epchtien; Sammy Frenk; Amichay Hameir; Elizabeth Temkin; David Schwartz; Yehuda Carmeli (Microbiology Spectrum, 2024)
ABSTRACTTimely detection of carbapenem-resistant Acinetobacter baumannii (CRAB) carriers is essential to direct infection control measures. In this work, we aimed to develop a practical protocol to detect CRAB from screening samples. To choose a selective medium that detects CRAB with high sensitivity and specificity, 111 A. baumannii clinical isolates were inoculated on three types of agar: mSuperCARBA (SC), CHROMagar Acinetobacter (CaA), and modified CHROMagar Acinetobacter (mCaA) containing 4.5 mg/mL meropenem. SC was non-selective, CaA was the most sensitive (100%), but only moderately specific (72%), and mCaA was highly specific (97%) and sensitive (98%). Confirmation of the carbapenem-resistant phenotype using PCR-based detection of blaOXA-23, blaOXA-24, and blaOXA-58 genes was specific but not sensitive, detecting only 58% of CRAB isolates. Identification of A. baumannii using either gyrB or blaOXA-51 PCR was excellent. Next, we used the same methodology in routine screening for CRAB carriage. mCaA had the best yield, with high sensitivity but moderate specificity to differentiate between CRAB and other carbapenem-resistant organisms. Skin sampling using sponges and 6 hour enrichment was highly sensitive (98%), while other body sites had poor sensitivity (27%– 41%). Shorter incubation had slightly lower yield, and longer incubation did not improve the detection. Performing PCR for blaOXA-51 and gyrB on colonies growing on modified mCaA differentiated between CRAB and other species with high accuracy (98% and 99%, respectively). Based on our results, we present a procedure for easy and reliable detection of CRAB carriage using skin sampling, short enrichment, selection on mCaA, and PCR-based identification.IMPORTANCECarbapenem-resistant Acinetobacter baumannii (CRAB) is a substantial cause of nosocomial infections, classified among the most significant multidrug-resistant pathogens by the World Health Organization and by the US Centers for Disease Control. Limiting the spread of CRAB is an important goal of infection control, but laboratory methods for identification of CRAB carriers are not standardized. In this work, we compared different selective agar plates, tested the efficiency of A. baumannii identification by PCR for species-specific genes, and used PCR-based detection of common resistance genes to confirm the carbapenem-resistant phenotype. During a prospective study, we also determined the optimal sample enrichment time. Based on our results, we propose a simple and efficient protocol for the detection of CRAB carriage using skin sampling, short enrichment, selection on appropriate agar plates, and PCR-based identification, resulting in a turn-around time of 24 hours.